2012
DOI: 10.1111/j.1654-109x.2012.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate effects on seed bank and vegetation composition of temperate grasslands

Abstract: Questions: Intensification of livestock production has led to the increasing input of agrochemicals, mostly herbicides, in natural and semi-natural grasslands. Glyphosate application shifts vegetation composition of grasslands of the Flooding Pampa region. Consequently, we asked two questions: (1) does the application of glyphosate affect the size, composition and diversity of the seed bank of these grasslands; and (2) to what extent does seed bank determine the vegetation composition of grassland communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 69 publications
1
9
0
3
Order By: Relevance
“…Nevertheless, 3 years of removals were not enough to decrease the differences between removal and non‐invaded communities, which may suggest that longer experiments and/or further restoration strategies are needed. In addition, herbicide application was the only treatment that increased the differences in species composition to non‐invaded communities, suggesting that besides removing E. plana , glyphosate may have other non‐target effects on natural vegetation (Rodriguez & Jacobo ). This finding has practical relevance, as glyphosate application is the most common method used for E. plana control in southern Brazil's grasslands, which may have further important implications for biodiversity conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 3 years of removals were not enough to decrease the differences between removal and non‐invaded communities, which may suggest that longer experiments and/or further restoration strategies are needed. In addition, herbicide application was the only treatment that increased the differences in species composition to non‐invaded communities, suggesting that besides removing E. plana , glyphosate may have other non‐target effects on natural vegetation (Rodriguez & Jacobo ). This finding has practical relevance, as glyphosate application is the most common method used for E. plana control in southern Brazil's grasslands, which may have further important implications for biodiversity conservation.…”
Section: Discussionmentioning
confidence: 99%
“…increasingly difficult to use because of popular sentiment. Herbicides may have negative effects on native species (Cornish and Burgin 2005;Rinella et al 2009;Rodriguez and Jacobo 2013), but in systems such as California grasslands, where exotic species exert a strong competitive effect on native survival, the net effect of herbicides is usually positive .…”
Section: Resultsmentioning
confidence: 99%
“…Prior research in other systems have demonstrated an effect of cropping system (Cardina et al 2002;Harbuck et al 2009;Legere et al 2011), including crop sequences of genetically engineered (GE) crops (Bohan et al 2011) on a regional basis, but these relationships have been limited to broad categorizations of the weed seedbank (e.g., monocotyledons and dicotyledons) and not a multivariate community-based assessment. Outside of row cropping systems, glyphosate applications can cause dramatic shifts in the seedbank composition of managed pastures (Rodriguez and Jacobo 2013). Based upon the results of surveying the emerged weeds in these fields (Young et al 2013), we expected the weed flora in the soil seedbank across broad regions of the U.S. in agricultural fields to show a signal in response to the rotation of GR traits and crops.…”
mentioning
confidence: 99%